The Role of TCF7L2 rs7903146 in Diabetes After Kidney Transplant: Results From a Single-Center Cohort and Meta-Analysis of the Literature. Issue 8 (August 2016) - Quaglia, Marco; Terrazzino, Salvatore; Musetti, Claudio; Cargnin, Sarah; Merlotti, Guido; Cena, Tiziana; Stratta, Piero; Genazzani, Armando
Abstract : Background: Several genetic polymorphisms modulate the risk of posttransplant diabetes mellitus (PTDM), a complication associated with an increased morbidity and mortality after kidney transplantation; however, their clinical utility is still undefined. Methods: Genetic analysis was performed in 464 kidney transplantation recipients to evaluate whether transcription factor 7-like 2 ( TCF7L2 ) rs7903146 gene polymorphism is associated with the risk of PTDM and a meta-analysis of similar studies including our results was performed (total kidney transplantation recipients, n = 3105). A predictive model of PTDM was built on the basis of this polymorphism and clinical parameters. Results: In our cohort, 163 patients possessed the CC genotype of rs7903146 (35.1%), 237 were CT (51.1%), and 64 were TT (13.8%): their 2 years PTDM incidence was, respectively, 7.8%, 11.9%, and 22.7%. At multivariate analysis, age (per year; hazard ratio [HR], 1.029; 95% confidence interval [95% CI], 1.005-1.054; P = 0.017), body mass index (25.0-29.9 vs <25.0; HR, 2.43; 95% CI, 1.40-4.23; P = 0.0018; ≥30 vs <25.0; HR, 5.70; 95% CI, 2.77-11.74; P < 0.0001), TCF7L2 rs7903146 (per each T allele; HR, 1.81; 95% CI, 1.26-2.59; P = 0.001) and previous transplants (HR, 2.80; 95% CI, 1.39-5.64; P = 0.004) emerged as independent predictive factors for PTDM. Meta-analysis of present and 5 previous studies showed higher risk of PTDM in carriers of rs7903146 TT genotype (odds ratio, 1.95; 95% CI, 1.39-2.74; P < 0.0001) and absence of heterogeneity among studies (I 2 = 0%). Inclusion of this polymorphism in a predictive model appeared to improve its ability to stratify patients according to the risk of PTDM. Conclusions: In renal transplant patients, TCF7L2 rs7903146 is strongly and independently associated with PTDM and might hold the potential to identify patients at risk for this complication. Abstract : From a single center retrospective study and a meta-analysis, the authors outline the role of the rs7903146 variant of the transcription factor 7-like 2 gene, which is associated with an increased risk of developing PTDM after kidney transplantation. Supplemental digital content is available in the text.